Improved quality control of [177Lu]Lu-PSMA I&T - Martin Kraihammer; Piotr Garnuszek; Andreas Bauman; Michael Maurin; Manuel Alejandre Lafont; Roland Haubner; Elisabeth von Guggenberg; Michael Gabriel; Clemens Decristoforo (EJNMMI Radiopharmacy and Chemistry, 2023)
Abstract Background Targeted radionuclide therapy with [177Lu]Lu-PSMA I&T (zadavotide guraxetan) has proven high efficacy and safety in treating patients with advanced prostate cancer worldwide. Several methods to determine the radiochemical purity have been reported but also limitations in the HPLC analysis due to retention of the sample and tailing effects when using standard gradients containing trifluoroacetic acid (TFA). We here report on the validation of a method for quality control of [177Lu]Lu-PSMA I&T including determination of radiochemical purity, identity testing and limit test for PSMA I&T by HPLC using a Phosphate buffer /Acetonitrile gradient system, complemented with a TLC system with 0.1N Citrate buffer pH 5 as mobile phase including validation of the methods, batch and stability data as well as identification of the main radiochemical impurity by mass spectrometry. Results The described HPLC method met the defined acceptance criteria in terms of accuracy, specificity, robustness, linearity, range and LOQ. HPLC analysis revealed symmetrical peaks and quantitative recovery from the column. Batch data showed a radiochemical purity > 95% as determined by HPLC, stability data a pronounced degradation due to radiolysis, which could be limited by addition of ascorbic acid, dilution and storage at low temperatures. The main radiochemical impurity was found to be the de-iodinated form of [177Lu]Lu-PSMA I&T. TLC analysis allowed to determine the amount of free Lu-177 even in the presence of DTPA in the final formulation. Conclusion Overall the described combination of HPLC and TLC provides a reliable tool for quality control of [177Lu]Lu-PSMA I&T.